2021
DOI: 10.3389/fmicb.2021.637834
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography, Bacterial Carrying Capacity, and the Prospect of Microbiome Manipulation in the Sea Anemone Coral Model Aiptasia

Abstract: Aiptasia is an emerging model organism to study cnidarian symbioses due to its taxonomic relatedness to other anthozoans such as stony corals and similarities of its microalgal and bacterial partners, complementing the existing Hydra (Hydrozoa) and Nematostella (Anthozoa) model systems. Despite the availability of studies characterizing the microbiomes of several natural Aiptasia populations and laboratory strains, knowledge on basic information, such as surface topography, bacterial carrying capacity, or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 93 publications
2
46
0
Order By: Relevance
“…Future laboratory work should attempt to carefully manipulate associations between different coral genotypes and microbial symbiotic partners (including Symbiodiniaceae and bacteria) to move toward the generation of gnotobiotic (i.e., known-microbiome) corals for use in functional experiments. This has been shown to be feasible in cnidarian model systems such as Hydra, Nematostella, and Aiptasia (Murillo-Rincon et al, 2017;Domin et al, 2018;Medrano et al, 2019;Costa et al, 2021;Dungan et al, 2021), but is only beginning to be explored in reefbuilding corals and other cnidarians (Lin et al, 2019;Cunning and Baker, 2020;Weiland-Bräuer et al, 2020). Experiments that apply a combination of antibiotics treatments followed by targeted probiotic delivery or "microbiome recovery" treatments will yield insights into whether disturbed coral-associated bacteria communities and host stress response phenotypes can be "rescued" by the re-introduction of one or several beneficial microbes (Peixoto et al, 2017(Peixoto et al, , 2021Rosado et al, 2018;Damjanovic et al, 2019;Assis et al, 2020;Santoro et al, 2021).…”
Section: Implications For Coral Conservation and Disease Intervention...mentioning
confidence: 99%
“…Future laboratory work should attempt to carefully manipulate associations between different coral genotypes and microbial symbiotic partners (including Symbiodiniaceae and bacteria) to move toward the generation of gnotobiotic (i.e., known-microbiome) corals for use in functional experiments. This has been shown to be feasible in cnidarian model systems such as Hydra, Nematostella, and Aiptasia (Murillo-Rincon et al, 2017;Domin et al, 2018;Medrano et al, 2019;Costa et al, 2021;Dungan et al, 2021), but is only beginning to be explored in reefbuilding corals and other cnidarians (Lin et al, 2019;Cunning and Baker, 2020;Weiland-Bräuer et al, 2020). Experiments that apply a combination of antibiotics treatments followed by targeted probiotic delivery or "microbiome recovery" treatments will yield insights into whether disturbed coral-associated bacteria communities and host stress response phenotypes can be "rescued" by the re-introduction of one or several beneficial microbes (Peixoto et al, 2017(Peixoto et al, , 2021Rosado et al, 2018;Damjanovic et al, 2019;Assis et al, 2020;Santoro et al, 2021).…”
Section: Implications For Coral Conservation and Disease Intervention...mentioning
confidence: 99%
“…In a recent step towards development of gnotobiotic E. diaphana , a method for bacterial depletion was reported [33, 34]. Depletion was achieved by exposure to four antibiotics with different mechanisms of action, and detection of bacteria in the treated anemones was by culture methods and PCR.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of bacterial uptake by the host may be due to failure of the selected bacteria to be recognized as symbionts by the host, control of bacterial adhesion as described by the bacteriophage adherence to mucus model (Barr et al 2013), or founder effects whereby existing bacterial communities influence the identity of new associates (Apprill et al 2012). Further, the ciliated surface of E. diaphana may play a role in preventing bacterial adhesion (Costa et al 2021). The three-dose strategy employed in the present study was similar to previous cnidarian experiments.…”
Section: Uptake Of Frs Bacteria By E Diaphana Was Short-livedmentioning
confidence: 99%
“…Although previous studies have demonstrated that bacterial inoculation can protect E. diaphana from pathogenic infection (Alagely et al 2011;Zaragoza et al 2014), incorporation of the selected bacteria into the host microbiome was not assessed. Recently, Costa et al (2021) showed that E. diaphana is resistant to microbiome changes as transplantation of either the Acropora humilis or Porites sp. associated microbiomes failed to shift the community composition compared to Exaiptasia microbiome controls.…”
Section: Uptake Of Frs Bacteria By E Diaphana Was Short-livedmentioning
confidence: 99%
See 1 more Smart Citation